Fabrication and Analysis of the HLM Method of Layered Polymer Bumper with the Fracture Surface Micrographs. (4th October 2022) - Narashima Rao, P. V.; Periyasamy, P.; Bovas Herbert Bejaxhin, A.; Vetre Selvan, E.; Ramanan, N.; Vasudevan, N.; Elangovan, R.; Tufa, Mebratu
Abstract : Bumpers are essential components that shield passenger cars from slow-speed collisions. Automobiles have them mounted on the front and rear ends. It is believed that bumpers would be crucial in avoiding or restricting damage to automobiles. Various composite material combinations are being researched when a car frontal accident occurs in light of the impact requirements. By comparing it to the parent material, the unique hybrid fibre-metal laminate production clarifies problems such as deformation and stress. This research focuses on identifying the hybrid material composed of basalt fibre with aluminium and glass fibre combinations, inducing it with the properties of the existing parent material and fusing it together to form a laminated composite. It also focuses on identifying its specific features and mapping them with those of the existing ones. This project's peculiarity strives to give the best bumper with a range of deformation between 0.017378 m and 0.03114 m for the 38 MPa tensile strength with a maximum stress prediction of 2.424 × 10 2 MPa that shows advantageous in day-to-day operations, and this is done by comparing simulation results.